The adventures of Vin Fiz - Cussler, Clive; Farnsworth, Bill (New York : Philomel Books, 2006)
Ten-year-old twins Casey and Lacey fly an enchanted, antique airplane, named the "Vin Fiz," across the United States and have several daring adventures along the way. Includes historical notes on the real "Vin Fiz," the name of the airplane that made the first transcontinental flight in 1911.
Keywords: Airplanes -- Fiction; Voyages and travels -- Fiction; Rescues -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Magic -- Fiction